DISCOURSE MARKERS IN VOGUE’S 73 QUESTIONS WITH ADELE - Frina Diniarta Nur; Rini Adriati; Lorensia Maria De Lores (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2023)
This study aims to find out what discourse markers are usually contained in an utterance, then what is the function of using these discourse markers, and also the reasons for using discourse markers that occur in Adele's video interview with Vogue. The data used in this study was obtained from the YouTube video content belonging to the Vogue channel called 73 Questions. As a basis for this research, there are several theories used, namely the theory of Fraser (2009), Dumlao and Wilang (2019), and Schiffrin (1987) in Cambridge (2018). In analyzing the data, the author uses a qualitative method with a case study research design. Based on the results of the analysis obtained by the author, it was found that 373 data were showing the use of discourse markers consisting of 26 different discourse markers. The 26 markers consist of 5 different types of discourse markers which include contrastive discourse markers, elaborative discourse markers, inferential discourse markers, temporal discourse markers, and spoken discourse markers. Furthermore, the dominant types of discourse markers that occur are elaborative discourse markers occur 118 times and spoken discourse markers occur 130 times. As for its function, there are 8 functions, namely, connecting markers, managing information, response markers, the cause, the effect marker, a temporal adverb, a marker of time, a sign of rejection or contrast, as well as a marker that describes the closeness between the topic of the question and the idea. And the reason found for the use of discourse markers is to make the conversation that occurs flow, not stiff, natural, and meaningful between Adele and the interviewer.